PENGUATAN PENDIDIKAN KARAKTER PADA PEMBELAJARAN TEMATIK - Khairan Khairan (FITRAH: International Islamic Education Journal, 2023)
Based on the results of observations, teachers have an important role in implementing student character values. Class IV teachers at MIN 5 Banda Aceh City have applied character values to planning and implementation. However, the author sees that there are still some students who lack order in moral values among these students due to the incomplete application of character values. In addition, the author only wants to describe how and what are the obstacles in applying character values to thematic learning at MIN 5 in Banda Aceh city. Based on the background of the problems that have been raised, the formulation of the problem in this study is: (1) How is the implementation of strengthening character education in thematic learning planning at MIN 5 in Banda Aceh City? (2) How is the implementation of strengthening character education in implementing thematic learning at MIN 5 in Banda Aceh City?. This research is a quantitative research using descriptive method. The subjects in this study were one school principal and four grade IV teachers at MIN 5 Banda Aceh City. Data collection was carried out using lesson plans documentation, class observations, and interviews. Documentation is done by analyzing the class IV teacher's lesson plan to find out how the lesson plan was prepared by the school, whether the five character values that the author examined in the lesson plan have emerged. Then class observations were carried out to see the learning process carried out by class IV MIN 5 teachers in Banda Aceh City.